Heat transfer enhancement in fin and tube heat exchangers by introducing perforations on the fins - Denizli, Harun (Graduate School, 2024)
This study focuses on a parametric investigation aimed at improving the performance of heat pump systems. Heat pumps are systems capable of both heating and cooling processes under variable climatic conditions, and the optimal design of heat exchangers is crucial for energy efficiency. The type of fin used in these systems plays a critical role, with herringbone wavy fins being commonly employed in the industry due to their ability to increase the heat transfer surface area compared to flat fins. However, it is observed that herringbone wavy fins are not effective in heat transfer when frosting does not occur. To address this issue, the creation of turbulence by perforating fins has been proposed. Numerical analyses were conducted to examine the effect of these perforations. Initially, a verification analysis comparing the numerical model with experimental data was performed to ensure the accuracy of the model. Subsequently, parametric analyses were carried out for different Reynolds numbers (600, 1200, and 1800) to evaluate performance. After determining the position and arrangement of the perforations, the influence of perforation shapes on performance was investigated. Although there were variations in friction and Colburn factors among different perforation shapes, the performance parameter remained consistent for each Reynolds number. Finally, the impact of varying perforation areas on performance was investigated. As the perforation area increased, the available surface area for heat transfer decreased, leading to a decrease in friction factor and an increase in heat transfer coefficient. Consequently, the performance parameter continuously increased as the perforation area increased. However, when considering the heat exchanger's capacity as a performance criterion, it was found that the perforation area should be approximately 15% of the total surface area to achieve maximum capacity. Therefore, the optimal perforation area for achieving maximum capacity was determined to be approximately 15% of the total surface area. (about 3 m/s).
Kanatlı borulu ısı değiştiricilerde kanatlara delikler açılarak ısı transferinin artırılması
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2024
Keywords: Fluid dynamics; Akışkanlar dinamiği; Heat exchangers; Isı değiştiriciler; Numerical analysis; Sayısal analiz